Profile Training: Basic Approaches to Content and Features - Khrienova, Viktoria (Pedagogical Discourse, 2012)
Existing approaches to understanding the features and characteristics of profile training are analyzed in the article. On the basis of the conducted analysis the main features of profile training are examined.